The Influence of Organizational Learning, Change Creation, and Team Orientation on Organizational Performance in the Regional Revenue Agency of DKI Jakarta Province - Rahman, Hasna Haningtyas; Sudibyo, Yvonne Augustine (Technium Social Sciences Journal, 2025)
The purpose of this study is to examine how team orientation, change management, and organizational learning strategies affect organizational performance. An organization’s performance is heavily influenced by a number of aspects, such as teamwork, organizational learning, and change implementation. The State Civil Apparatus (ASN) at the DKI Jakarta Provincial Revenue Agency is the study’s population. Non-probability sampling was the method employed for sampling in this investigation. 168 people made up the study’s sample. Responses from ASN Bapenda DKI Jakarta. Descriptive statistical tests, reliability tests, model accuracy tests, R-square tests, and partial least squares (PLS) analysis of the outer and inner models were used in the data testing process. The study’s findings led to the conclusion that team orientation, organizational learning, and creating change all significantly and favorably affect organizational performance. Since the Team Orientation variable has a significant impact on Organizational Performance, it is intended that the organization may further enhance its service to Team Orientation. If this is successful, Organizational Performance will improve.